Perancangan Buku Infografis Rumah Adat Batak Toba Sebagai Upaya Pelestarian Ragam Hias - Adiski, Sri Nanda; Ghifari, Muhammad; Putri, Aji Sofiana (Universitas Utpadaka Swastika, 2024)
Samosir is an island located in the middle of Lake Toba, North Sumatra Province. The tribe that inhabits this island is the Toba Batak tribe. One of its cultures is the traditional house and is a cultural wealth that should be preserved. Simanindo Village is one of the villages that still maintains the Toba Batak Traditional House. However, as time goes by and the location is far away, many young people do not know and understand about the Toba Batak traditional house. The preservation of Toba Batak culture can be threatened if the younger generation lacks knowledge about traditional houses. The purpose of this design is to create an infographic book that contains information about the Toba Batak Traditional House and its decorations that can collaborate with the local Tourism Office and Museum. This design uses the design thinking method and data analysis using SWOT. The final result of this design is an infographic book and supporting works in the form of tote bags and key chains.